Challenges of creating cities in China: Lessons from a short-lived county-to-city upgrading policy - Fan, Shenggen; *Li, Lixing; Zhang, Xiaobo (Journal of Comparative Economics, 2012)
Fan, Shenggen, Li, Lixing, and Zhang, Xiaobo-Challenges of creating cities in China: Lessons from a short-lived county-to-city upgrading policy #n#It has been widely observed that China is under-urbanized. The central government has tried to use various policies to promote urbanization. In this paper, we evaluate one of these policies - count-to-city upgrading. Under China's hierarchical governance structure, a city status can only be determined and awarded by the central government. In the 1980s and 1990s, China adopted a formula-based county-to-city upgrading policy. Based on a large panel dataset covering all counties in China, we find that the formula was not strictly enforced in the practice. Moreover, jurisdictions that were upgraded to cities prior to 1998 do not perform better than their counterparts that remained county status in terms of both economic growth and providing public services. Largely because of these problems, this policy was called off in 1997. Given the strong need for urbanization, more indigenous institutional innovations are needed to find a viable way of creating cities, which would also provide compatible incentives to local governments. Journal of Comparative Economics 40 (3) (2012) 476-491. International Food Policy Research Institute (IFPRI), Washington, DC, United States; China Center for Economic Research, National School of Development, Peking University, Beijing 100871, China. (C) 2012 Association for Comparative Economic Studies Published by Elsevier Inc.
Keywords: Urbanization; City creation; Governance structure; Political centralization; China